Redes técnicas e o papel de Anápolis no contexto da rede urbana regional - Rodrigues, Lucas Kallil de Paula (2022)
Spatial strategies for the use and control of the territory inevitably permeate the appropriation of technical networks, which constitute indispensable supports in the articulation and performance of various activities, especially economic ones, as they directly influence the flow and circulation of goods, people , information and loads in the territory. Furthermore, as a structuring element of a territory, networks are permeated with meanings, interests and political actions. In this sense, analyzing the city of Anápolis is to place itself before a different context in relation to nearby cities: what led this city to stand out regionally and become a regional centrality, even if located between two large metropolises. With that in mind, the objective of this study was to analyze the technical networks as structuring elements of the process of formation of Anápolis and its centrality and to understand the role of this city in the context of the regional urban network. Therefore, we studied the concept of technical networks and their perspectives in the context of territorial formation, which were observed from three points. The first, based on a review of networks, technical networks and urban networks. The second, from the understanding of the influence and impacts of networks in the process of territorial formation of Anápolis – from the genesis to the 21st century. And, finally, seeking to synthesize the scales of interaction of Anápolis in the context of the regional urban network and the corporate use of the territory from a central question: who benefits from this space and networks? The methodological procedures were based on bibliographic research, documental research in printed and electronic collections of public and private institutions, fieldwork and mapping. The path taken revealed that technical networks have a central role in the process of formation and consolidation of Anápolis. From them, the city consolidated itself as an important regional center and extended its region of influence (regional urban network). However, as the networks permeate a series of elements and interests intrinsic to them, as actors of different groups, benefited and excluded in their conception and use, construction and deconstruction of spaces and hierarchies, we observe that, in the case of Anápolis, technical networks (roads, railways, electricity and logistical infrastructures) have become increasingly subordinated to the commands of corporate groups that have expanded their control systems and porosity in the choices of the functions of the technical networks circumscribed in Anápolis territory. Thus, the formation of a city with an eminently strategic position was consolidated, pulverized by technical networks and junctions of different matrices, and with a relevant centrality, but in which the use and production of the territory meet, for the most part, the demands of hegemonic actors.